THE EFFECTS OF EXECUTIVE COMPENSATION AND CORPORATE GOVERNANCE ON PAYOUT POLICY IN UK - Adilah Azhari, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
: The study investigates how corporate payout policy is influenced by CEO share ownership, CEO stock options and CEO long-term incentive plans (LTIPs) in UK firms from 2006 to 2015 using Tobit regressions (for total payouts, dividends and share repurchases) and logistic regressions for the propensity of firms paying out to shareholders. The results show that CEO share ownership LTIPs have positive effects on corporate payout policy. In contrast, corporate governance characteristics do not show conclusive results which affect changes in payout policy. Dividend payout is significantly influenced by CEO share ownership compared to share repurchase payout. The findings support the notion that CEOs’ share equity ownership is used to align managerial interest with shareholders in terms of cash payouts to shareholders.